Modern information technologies in education system (Eurasian Journal of Philology Science and Education, 2018)
This publication offers a different approach to the uses of learning technologies in the language classroom.Using of ICT in the learning process makes it possible to activate the cognitive, mental and independent activity of the students , to intensify the learning process .The main task of teaching foreign languages (FL) is forming and developing communicative culture of students, teaching practical using foreign languages.Nowadays, the introduction of the personal computer, multimedia technology and global information network Internet affects the education system, causing significant changes in the content and methods of teaching foreign languages.